Are Capillary Whole Blood Coagulation Monitors Suitable for the Control of Oral Anticoagulant Treatment by the International Normalized Ratio? - Tripodi, Armando; Arbini, Arnaldo A; Chantarangkul, Veena; Bettega, Donato; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1993)
The 512 Coagulation Monitor is a portable coagulation photometer that uses disposable cartridges containing a lyophilized rabbit brain thromboplastin to measure the PT for capillary whole blood. It has been proposed as a suitable system for patient self monitoring at home, but its performance has never been thoroughly assessed for results expressed as International Normalized Ratio (INR). In particular, there is no available information about the adequacy of the WHO calibration model with the Monitor. The aims of the study were to determine the International Sensitivity Index (ISI) against the secondary International Reference Preparation for rabbit thromboplastin and to assess the precision of the INR. The study demonstrates that the Monitor can be calibrated with the WHO model, because log-transformed PTs for patients stabilized on oral anticoagulants and normal individuals are linearly related and because the same orthogonal regression line describes patient and normal data points adequately. However, the ISI calculated in this study (2.715) is higher than that adopted by the manufacturer (2.036). The between-assay reproducibility of the Monitor is acceptable (CV = 9.7%) with results expressed in seconds, but become unacceptably poor when the results are converted into INR (CV = 18.8%) because of the high ISI value of the thromboplastin used. We think that the Monitor might be suitable for monitoring oral anticoagulant therapy if the manufacturer would provide a more sensitive thromboplastin in the cartridges.